The numbers -9 and -4 add up to -13 and multiply to get 36
I hope this helped :)
If you look at the graph of sin(n), you can notice that it oscillates every kpi/2 when k is odd. This oscillation proves that sin(n) diverges.
Answer:
Step-by-step explanation:
hello :
3b^4−6b^2+27b = 3b(b^3-2b+9)
Answer:
- attached graph
- Horizontal Asymptote: y = 5
- twon whole number points are (4,4) and (5,1)
Step-by-step explanation:
- Exponential functions have a horizontal asymptote. The equation of the horizontal asymptote
y = -4^(x-4) + 5
= -4^(4-4) + 5
= -4^(0) + 5
= -1 + 5
= 4
y = -4^(x-4) + 5
= -4^(5-4) + 5
= -4^(1) + 5
= -4 + 5
= 1
The value of p = 11
y = 5x + p
1 = 5(-2) + p
1 = -10 + p
11 = p